PENINGKATAN KETERAMPILAN MENULIS TEKS BERITA MENGGUNAKAN METODE MIND MAPP PADA SISWA KELAS VIII C SMP AL ISLAM CIPARI KABUPATEN CILACAP - Itmamun Ibad; Wijaya Heru Santosa (CARAKA, 2016)
This study aimed to describe (1) describe an increase in the activity of students in writing a text message using the method described MIND MAPP and (2) capacity building students in writing a text message using MAPP MIND method class VIII C SMP Al Islam Cipari Cilacap. This research is a classroom action research (CAR) is carried out in two cycles.The subject this study were all students of class VIII C SMP Al Islam Cipari which amounted to 37 students.Objects this study is subject to the basic competence Indonesian write a brief news text, solid, and clear.The instrument used is observation sheet, interview guides for teachers and students, student worksheets, and documentation. Data were analyzed qualitatively based on the reflection of each cycle of action. The results of this study indicate that the Mind Mapp learning methods can enhance the activity of class VIII C SMP Al Islam Cipari Cilacap on the process of learning to write news text. This is evident from the increased activity of students in each cycle. Students' creativity in writing a text message on pre-cycle  40.54%, the first cycle 67.56%  and the second cycle 89.16%. Attention students in teacher attention on pre-cycle  37.83%,  the first cycle 72.97%, and the cycle II 83.73%. The activity of students in group discussions on pre-cycle  43.24%, the first cycle 67.56%  and the second cycle 86.48%. Cooperation with well in discussions pre cycle group at 45.94%, the first cycle 64.86% and the second cycle 89.18%. Mind Mapp learning methods to improve the ability to write a text message class VIII C SMP Al Islam Cipari Cilacap. It can be seen from the aspect of the content of the idea on pre-cycle 29.72%, the first cycle 56.75%  and the second cycle 94.59%. The accuracy of the contents of the organization pre-cycle 37.83%, the first cycle 70.27%  and the second cycle 89.18%. The accuracy of grammar, pre-cycle 35.13%, the first cycle 62.16%  and the second cycle 89.18%. The use of structures and vocabulary in pre cycle 32.43%, the first cycle 64.86%  and the second cycle 89.18%. The use of the spelling of text in pre-cycle  35.13%, the first cycle 67.56%  and the second cycle 91.89% Thus, the use of Mind Mapp method can increase the activity and the ability writing text news.